Mixed Convection in a Lid Driven Cavity With Inclined Magnetic Field Using COMSOL - Amir, Nur Athirah; Muhamad Ghazali Kamardan (Enhanced Knowledge in Sciences and Technology, 2024)
This study investigate how heat transmission and fluid flow is influenced by the magnetic field’s inclination in a two-dimensional square cavity. The top moving lid was retained at a heated temperature, while the lower wall was retained cold and two vertical walls were well insulated. This analysis of the streamlines and isotherms plot was performed by using COMSOL software. It was found that a stronger magnetic field resulted in a decreased heat transfer rate. Furthermore, this magnetic field slowed down the flow of mixed convection.